2022
DOI: 10.12793/tcp.2022.30.e5
|View full text |Cite
|
Sign up to set email alerts
|

Stability of acetylsalicylic acid in human blood collected using volumetric absorptive microsampling (VAMS) under various drying conditions

Abstract: Acetylsalicylic acid (ASA) is one of the most commonly used medications in global market, with a risk of intoxication in certain patients. However, monitoring blood drug concentration often requires frequent hospital visits; hence there is an unmet need to increase patient-centricity by conducting blood sampling at home. Volumetric absorptive microsampling (VAMS) is a device that allows collection of homogenous and accurate volume of blood without venipuncture, and can be utilized by patients who are not in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 27 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…showed that humidity control was critical for its stability, and the use of a simple household vacuum sealer could maintain the stability for up to 1 month. 33 Similar to DBS filter paper modifications, the polymeric tips can be modified to attain new features.…”
Section: Volumetric Tip Microsamplingmentioning
confidence: 99%
See 3 more Smart Citations
“…showed that humidity control was critical for its stability, and the use of a simple household vacuum sealer could maintain the stability for up to 1 month. 33 Similar to DBS filter paper modifications, the polymeric tips can be modified to attain new features.…”
Section: Volumetric Tip Microsamplingmentioning
confidence: 99%
“…Nevertheless, different drying conditions, such as the use of a desiccator, pressurization, nitrogen gas and household vacuum sealer, have been shown to improve sample stability. In the analysis of acetylsalicylic acid, a hydrolysis‐prone analyte, Moon et al showed that humidity control was critical for its stability, and the use of a simple household vacuum sealer could maintain the stability for up to 1 month 33 …”
Section: Microsampling Technologies and Innovationsmentioning
confidence: 99%
See 2 more Smart Citations